A Partial History of South–South Art Criticism: Juan Dávila's Collaborations with Art & Text and Chilean Art Workers during the Pinochet Dictatorship, 1981–1990. Issue 6 (2nd November 2021) - Tello, Verónica; Valenzuela-Valdivia, Sebastián
Abstract: From 1981 to 1990, the Australian art journal Art & Text and the affiliated Art & Criticism Monograph Series had a productive, if at times fragmented, relationship with a small but influential group of Chilean arts workers during the Pinochet regime (1973–1990). Initiated by the Australian-Chilean artist, Juan Dávila, this collaboration — including key figures such as Paul Taylor, Paul Foss, Nelly Richard, Patricio Marchant and Francisco Zegers − gave rise to multiple and significant essays, books and translations that contested the limits of Pinochet's epistemological frontiers on the one hand, and Euro-North American centrist readings of the artworld on the other. This article returns to several archives across Australia and Chile to trace the simultaneous developments of southern thinking, and asks what can be learned about the co-production of epistemologies across two distinct Pacific locations. The almost instant anachronism of art criticism, especially that on the margins, has meant that Art & Text 's and the Art & Criticism Monograph Series 's history of supporting Chilean art writing during the dictatorship has not been effectively transmitted into the present. It is, by now, pretty much unknown or forgotten in both Australia and Chile − and elsewhere − awaiting the attention of a younger generation of art workers hoping to connect to these fragmented histories.